Spatial analysis and characterization of sexual violence against children and adolescents in Bahia (Research, Society and Development, 2020)
The study aimed to analyze the phenomenon of sexual violence against children and adolescents in the state of Bahia, between 2014 and 2016, since its characterization to spatial relations. This is an ecological study of reported cases of sexual violence in children and adolescents, which occurred in Bahia, with sociodemographic characterization of cases, occurrences and aggressors; time trend of rates and Moran statistic I for spatial analysis. A total of 2,443 cases were reported, the victims were mostly female (85.2%), mean age 12 years and brown (69.3%); the aggressors were known (44.2%) and males (95.0%). In relation to the distribution of rates, there was a variation from 1.7/100,000 inhabitants in January 2014 to 1.0/100,000 inhabitants in December 2016. In spatialization, there was an incidence of the phenomenon in almost all of the municipalities of Bahia (96%) with high-high cluster formation at approximately 6%. Thus, it is concluded that children and adolescents are potentially exposed to sexual violence. The spatialization of cases opens a range of possibilities for planning health surveillance strategies, aiming at more assertive interventions.